Position Identification Method of Isolation Switch for Prosumer Substation Based on Intelligent Image Recognition Technology - Wang, Bozhong; Wei, Juan; Li, Peng; Peng, Mai; Li, Cheng; Wang, Lide; Zhou, Hui; Yi, Jin (Frontiers in Energy Research, 2022)
To improve the intelligence and automation for adapting to the development of prosumer substations, this paper proposes an isolation switch opening and closing position discrimination method based on intelligent image recognition technology. The marking point recognition and edge detection method based on the Canny algorithm is proposed to identify the open and close position of disconnecting switch. Compared with the traditional auxiliary switch contact, the proposed method can form the “double confirmation” criterion of non-homologous position to realize the open and close position of the disconnecting switch, while providing the auxiliary discrimination support for one-button compatible operation. In addition, in order to better apply to the prosumer substation, the transformation scheme of intelligent recognition and monitoring of the disconnecting switch is designed in the high voltage environment of the substation. The field work proves that the designed system has good accuracy and reliability, which can enhance the development of one-button sequence control technology and the implementation and application in the construction site.